TOXIC AND ESSENTIAL METAL CONCENTRATIONS IN ROASTED PLANTAIN AND FISH COMMONLY CONSUMED BY PORT HARCOURT INHABITANTS, RIVERS STATE, NIGERIA - Dumka, Nwineewii Jack; Marcus Abiye Clement (Acta Scientiae et Intellectus, 2024)
Of recent, the consumption of roasted Plantain and fish popularly known as Bole during lunch hours in Port Harcourt has been on the increase. Considering the open nature by which this meal is prepared along roadside and the industrial concentrations of the Port Harcourt metropolis, most inhabitants of the city believed that these food items may have been polluted by metals. Hence, this study was necessitated to actually ascertain the levels of some toxic and essential metals in roasted plantain and fish in the city. Food samples were collected from eight locations based on high population of the area, high vehicular movements and presence of industries. The collected food samples were prepared, digested and subjected to heavy metals analyses using the atomic absorption spectroscopy. The results of the detectable concentrations (mg/kg) of the metals in the roasted plantain were: Cd (0.062±0.1289) mg/kg, Pb (0.135±0.1207) mg/kg, Zn (21.33±13.203) mg/kg, Fe (58.19±14.73) mg/kg, Cr (0.054±0.3002) mg/kg, Mn (0.026±0.0273) mg/kg, Ag (0.036±0.0197) mg/kg and As (0.038±0.0243) mg/kg. In the roasted fish the mean concentrations with standard deviation were: Cd (0.007±0327) mg/kg, Pb (0.07±0.066) mg/kg, Zn (29.6±27.34)mg/kg, Fe (44.103±19.838)mg/kg, Cr (0.64±0.289)mg/kg, Mn(0.03±0.0192) mg/kg, Ag(0.0215±0.0174) mg/kg and As(0.0145±0.0141)mg/kg. These results showed that the mean concentration of all the essential metals in roasted plantain and fish were within the recommended limit set by WHO/FAO. For the heavy metals, the mean concentrations were within the recommended limits in the plantain and fish except in few locations where the concentrations of Pb, Cd, Ag and As were slightly elevated. Based on the findings, roasted plantain and fish may be considered fit for consumption. The slight increase in concentration at some locations however calls for caution considering the nonbiodegradable nature and accumulative properties of heavy metals.